Association of Grain Iron and Zinc Content With Other Nutrients in Pearl Millet Germplasm, Breeding Lines, and Hybrids - Govindaraj, Mahalingam; Kanatti, Anand; Rai, Kedar Nath; Pfeiffer, Wolfgang H.; Shivade, Harshad (Frontiers in Nutrition, 2022)
Micronutrient deficiency is most prevalent in developing countriesregions of the world, including Africa and South-East Asia where pearl millet (Pennisetum glaucum L.) is a major crop. Increasing essential minerals in pearl millet through biofortification could reduce malnutrition caused by such deficiency. This study evaluated the extent of variability for of micronutrients (Fe, Zn, Mn, Na) and macronutrients (P, K, Ca, Mg) and their relationship with Fe and Zn content in 14 trials involving pearl millet hybrids, inbreds, and germplasm. Significant genetic variability was found for the of macronutrients and micronutrients was found within and across the trials (Ca: 4.2 to 40.0 mg 100 g-1, Fe: 24 to 145 mg kg-1, Zn: 22 to 96 mg kg-1 and Na: 3.0 to 63 mg kg-1). Parental lines showed significantly larger variation for nutrients than hybrids, indicating their potential for use in hybrid parent improvement through recurrent selection. Fe and Zn contents were positively correlated and highly significant and positively correlated (r=0.58 to 0.81; P<0.01). Fe and Zn were positively and significantly correlated with Ca (r=0.26 to 0.61; P<0.05) and Mn (r=0.24 to 0.50; P<0.05). The findings Sindicate uggest joint selection for Fe, Zn and Ca will be effective. Substantial genetic variation and a high heritability (>0.60) for multiple grain minerals provide good selection accuracy prospects for genetic enhancement. Highly positive significant correlation between Fe and Zn and , also the non-signficant correlation of grain macronutrients and micronutrients with Fe and Zn suggests there is scope to achieve a higher levels of Fe/Zn simultaneously in current pearl millet biofortification efforts without affecting other grain nutrients. Therefore, high big prospects for improving multiple nutrients in pearl millet